Violating Peace : Sex, Aid, and Peacekeeping - Westendorf, Jasmine-Kim (Book collections on Project MUSE., 2020)
"This book is about the nature of sexual exploitation and abuse by interveners in peace operations, the significant and long-term impacts it has on the capacity and credibility of the international community involved in peacekeeping, and how policies can more effectively address this phenomenon in future peace operations"--